Determining the manner of death in victims in drug-induced psychosis: a case of an atypical head stab wound - Handlos, Petr; Klabal, Ondřej; Vojtek, Vladimír; Handlosová, Klára; Krejčí, Tomáš; Uvíra, Matěj (Forensic science, medicine, and pathology, 2024)
This case report presents a rare case of an atypical head stab wound suffered by a drug addict and inflicted with a screwdriver during drug-induced psychosis. It describes the diagnostic and treatment procedures in the hospital and the findings of the subsequent autopsy. It also analyzes the review of the interpretation of the CT scans made upon admission and the subsequent treatment by an independent medical review panel, which revealed signs of medical mismanagement. Therefore, it also discusses the legal consequences that the case may have involved for the attending physicians in addition to the consequences for the suspected perpetrator. The report raises many issues encountered in the case in terms of the clinical treatment and forensic determination of the manner of death in cases of injuries caused by sharp instruments and highlights the importance of comprehensive evaluation of the circumstantial evidence together with the clinical or autopsy findings, since such evidence may sometimes be overlooked in clinical practice.
Keywords: Humans; Head Injuries, Penetrating; bodné rány; Suicide; penetrující poranění hlavy; počítačová rentgenová tomografie; Psychoses, Substance-Induced; Wounds, Stab; Cavernous sinus; Tomography, X-Ray Computed; Drug-induced psychosis; toxické psychózy; Hemorrhagic shock; Stab wound; lidé; Screwdriver